2017
DOI: 10.3758/s13421-017-0735-y
|View full text |Cite
|
Sign up to set email alerts
|

Early markers of lexical stress in visual word recognition

Abstract: The goal of the present study was to investigate the time-course of suprasegmental information in visual word recognition. To this aim we measured event-related brain potentials (ERPs) during a simple lexical decision task in Italian. Two factors were manipulated: Stress dominance (the most frequent stress type) and stress neighborhood consistency (the proportion and number of existent words sharing orthographic ending and stress pattern). Participants were presented with target words either bearing dominant (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…In Dutch, Cutler and van Donselaar (2001) found that participants were less likely to reject a spoken pseudoword when the onset matched a real word both segmentally and in terms of stress than when it only matched segmentally. In Italian, Colombo and Sulpizio (2015;Sulpizio & Colombo, 2017) found that visually presented target words with the dominant stress pattern were responded to faster and more accurately than words with nondominant stress.…”
Section: Stress Effects In Word Recognitionmentioning
confidence: 99%
“…In Dutch, Cutler and van Donselaar (2001) found that participants were less likely to reject a spoken pseudoword when the onset matched a real word both segmentally and in terms of stress than when it only matched segmentally. In Italian, Colombo and Sulpizio (2015;Sulpizio & Colombo, 2017) found that visually presented target words with the dominant stress pattern were responded to faster and more accurately than words with nondominant stress.…”
Section: Stress Effects In Word Recognitionmentioning
confidence: 99%
“…These stress pattern distributions are mirrored in stress assignment performances (Colombo, 1992;Sulpizio & Colombo, 2017), as shown by studies investigating the interaction of word frequency and stress regularities in naming latencies of disyllabic words in L1 English (e.g., Monsell et al, 1989;Kelly et al, 1998) and in L1 Italian (Colombo, 1992;Colombo & Zevin, 2009;Sulpizio, Burani, & Colombo, 2015). When stress is defined as default on the first syllable of disyllabic words, as suggested by the studies of Chateau and Jared (2003), and Yap and Balota (2009), effects of regularity are found only in low frequency words and errors (Colombo, 1992;Perry et al, 2010).…”
Section: Word Stress Frequency Distributions In Brazilian Portuguese mentioning
confidence: 88%
“…There are at least two major differences that make comparison of our explanation and that put forward by Traficante et al (2011) difficult. Unlike Spanish, stress assignment is not usually orthographically marked in Italian and is unpredictable for words longer than two syllables (Colombo, 1992; Colombo & Zevin, 2009; Sulpizio & Colombo, 2017; Wilson, Ellis, & Burani, 2012). Moreover, the addition of a suffix might also imply the reassignment of the stress of the word (Traficante et al, 2011).…”
Section: Discussionmentioning
confidence: 99%